THE EFFECTIVITY OF MATCHING PAIRS MEMORY TWIST BLOCK ON KNOWLEDGE AND ATTITUDES TOWERDS ANTIKESAL (ANTICIPATING SEXUAL VIOLENCE ) IN FEMALE ADOLESCENT - Dewi, Triyana Puspa; Serinadi, Desak Made (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2026)
Introduction: Sexual violence as a worldwide issue nowadays has become an alarming condition among adolescents. Female adolescents as the common victims experienced traumatized situations that indicate the need for anticipatory intervention. This research aims to prove the effectiveness of matching pairs memory twist block on knowledge and attitude towards ANTIKESAL (Anticipation of Sexual Violence) in female adolescents.Method: This research is a quasi-experimental study using a one group pre-post design which involved 63 female students aged 14-17 years from SMK Kesehatan PGRI Denpasar. The sampling technique used is total sampling and analyzed by the paired t-test and Wilcoxon signed-rank test.Results: The results are displayed in this study: 66.7% are in the tenth grade, 92.1% live with their biological families, 58.7% have parents who earn less than the regional minimum wage, 50.8% of parents work in the private sector, 69.8% are not dating, and 81% have no history of violence or sexual violence. An increase in average scores following the intervention and a p-value < 0.05 demonstrate the effectiveness of the matching pairs memory twist block in raising knowledge (p-value = 0.001) and attitudes (p-value = 0.020) on ANTIKESAL in adolescent girls.Conclusions: The matching pairs memory twist block as a media of game is proven to effectively enhance the knowledge and attitudes toward anticipating sexual violence. The benefits of this research can be enhanced by modifying educational and interactive games based on local wisdom and incorporating sexual violence prevention education into the learning curriculum.